PENDAMPINGAN PENYUSUNAN RENCANA STRATEGIS DI SEKOLAH LUAR BIASA NEGERI WIRADESA KABUPATEN PEKALONGAN - Wijayanti, Dian; Kholifah, Nur; Murniati, Ngurah Ayu Nyoman (STKIP Pesisir Selatan, 2025)
The Strategic Plan is the strategic steps taken by the school to achieve the vision and dreams of an educational institution. SOAR analysis is an approach to strategic planning that focuses on strengths that can be used to support the achievement of targets and opportunities that can be used as strengths in the long term. SOAR stands for strengths, opportunities, aspirations, and results. The socialization participants were teachers and educational staff at SLB Negeri Wiradesa. Then conduct an interview and discussion process with teachers and education staff to identify existing problems in preparing the Strategic Plan; Literature research for reference materials used during this service activity; Assistance in preparing the Strategic Plan. Utilization of SOAR analysis as a support for the process of preparing the School Strategic Plan to improve the quality and management of schools, during the mentoring process based on the results of the teachers' discussions so that it is easier to draw conclusions. The output of this service activity is the Wiradesa State SLB strategy plan.